Analisa Dampak Sambaran Petir pada Peralatan NDB JTM-30C di Jakarta Air Traffic Services Center - Faisal, Mulya Permata Asa; Syafriwel, Syafriwel; Hidayat, Jhoni (Lembaga Yasin AlSys, 2024)
This study analyzes the impact of lightning strikes on the NDB JTM-30C equipment at the Jakarta Air Traffic Services Center (JATSC). NDB equipment is used in flight navigation, but lightning strikes can disrupt operations and flight safety. Data on lightning strikes and disturbances to the NDB were collected and analyzed. The results show a relationship between the frequency of lightning strikes and disturbances to the NDB. These disturbances can affect signal quality, cause temporary outages, or result in permanent damage to the equipment. The potential impact poses risks to flight safety and operational performance. Mitigation measures, regular maintenance, and early warning systems should be implemented to reduce the risks of disturbances caused by lightning strikes. This research provides a better understanding and a foundation for effective mitigation strategies to enhance flight safety.